Use of essential oils in the treatment of anxiety disorder in children: an integrative review (Research, Society and Development, 2022)
This article aimed to carry out an integrative review of the literature focused on the use and effectiveness of aromatherapy with essential oils (EO) in the treatment and control of anxiety in children. The PUBMED, LILACS, VHL and SCIELO databases were used, which, after the exclusion and inclusion criteria, included 11 studies related to the topic. The results show that EO's of lavender (lavandula angustifolia), orange (Citrus aurantium), sweet orange (Citrus sinensis) and bergamot (Citrusbergamia) were effective in reducing anxiety in children subjected to a stressful environment or situation. On the other hand, the use of bergamot (Citrusbergamia) EO in children with autistic aspect disorder did not reduce anxiety when compared to control. Overall, EO's are safe and effective in reducing anxiety in children with specific phobias, and there is a need for more studies in children with ASD to evaluate the use of other essential oils in reducing anxiety, as well as to analyze aromatherapy in groups of children. with different categories of anxiety disorder.